b ) x2 - 4x - 2y + xy + 1 = 0
( x2 - 4x + 4 ) - y ( 2 - x ) -3 = 0
( x - 2 )2 - y ( 2 - x ) = 3
( 2 - x ) ( 2 - x - y ) = 3
đến đây lập bảng tìm ra x,y
a) x2 + y2 + xy + 3x - 3y + 9 = 0
2x2 + 2y2 + 2xy + 6x - 6y + 18 = 0
( x2 + 2xy + y2 ) + ( x2 + 6x + 9 ) + ( y2 - 6y + 9 ) = 0
( x + y )2 + ( x + 3 )2 + ( y - 3 )2 = 0
\(\Rightarrow\)( x + y )2 = ( x + 3 )2 = ( y - 3 )2 = 0
\(\Rightarrow\)x = -3 ; y = 3
SKT_NTT câu b bạn làm rõ ra hơn có đc không
câu b ngang đó, lập bảng :
2-x | 1 | 3 | -1 | -3 |
2-x-y | 3 | 1 | -3 | -1 |
x | 1 | -1 | 3 | 5 |
y | -2 | 2 | 2 | -2 |
Vậy ( x ; y )